PENGARUH RASIO EFEKTIFITAS PENDAPATAN ASLI DAERAH DAN EFISIENSI BELANJA DAERAH TERHADAP KINERJA KEUANGAN DAERAH PADA DINAS LINGKUNGAN HIDUP PROVINSI DKI JAKARTA PERIODE 2018-2023 - Rahil, Rahil; Widodo, Dwiyatmoko Puji; Nuraeni, Yuni Siti (Universitas Nusa Cendana, 2024)
Regional Original Income (PAD) is the basis of regional financing, the ability of a region to explore PAD will have an impact on the growth and development of the region. One of the local government agencies responsible for environmental management is the DKI Jakarta Environment Agency. The purpose of this study is to find out how much the financial ratio affects financial performance: (1) The effectiveness of PAD on Regional Financial Performance (2) the efficiency of Regional Expenditure on Regional Financial Performance for the period 2018-2023.The samples used are the Budget Realization Report and the Performance Report of Government Agencies of the DKI Jakarta Provincial Environment Agency for the 2018-2023 Period which have been audited by the Financial Audit Agency (BPK). The results of this study show that (1) The effectiveness of PAD has an effect on Regional Financial Performance with a significant value of 0.036 (2) Regional Expenditure Efficiency has no effect on Regional Financial Performance with a significant value of 0.388 (3) The PAD Effectiveness Ratio and Regional Expenditure Efficiency together have a significant effect on Regional Financial Performance with a significant value of 0.035.